ANALISIS PENGUATAN PENDIDIKAN KARAKTER PADA BATIK GROMPOL DI GALERI BATIK SOENDARI - Belinda Dewi Regina; Arinta Rezty Wijayaningputri (Universitas Negeri Surabaya, 2021)
The value of foreign culture is currently growing so rapidly along with technological advances that are very real and change the values of local culture in Indonesia, one of which is batik. Most of the community, including students at universities, do not understand the local wisdom found in their area. There is a gallery in Malang with the name Soendari Gallery which has many kinds of batik based on Strengthening Character Education. The purpose of this study was to analyze the character load on Grompol batik. This study uses an approach with a descriptive type of research. The research subject is Grompol batik. Batik Grompol has a circle shape in which one of the five characters is gotong royong. There is also the kawung motif, which is known as a symbol of strength and justice, which is also one of the missionaries of character education. It can be said that in grompol batik contains character education.